Historic center of the city of Jáchal - San Juan - Argentina: guidelines for the conservation of its cultural heritage - Pochi Dorazio, Ana Valeria (2017)
The present work belongs to the "Management Plan of the Historical Center of the city of Jáchal", San Juan, Argentina, for its conservation, revitalization, recovery and valorization1. We started with the survey of each plot of the historic center with pre-established schedules, which took into account the most important variables such as the type of construction, style, status, heritage value and land use. The stages were carried out in phases: Survey in situ, Digitalization of data and Grid interpretation of data. As a final result, an analysis tool was obtained that combines urban photographic profiles and the graphic data of the historical center that made possible the corresponding diagnoses of the current situation of the analyzed zone and to be able to carry out the normative guidelines for the conservation and enhancement of the Center. Historical of Jáchal.